Modelization and analysis of dynamic heterogeneous redundant system. (13th October 2020) - Wang, Wei; Li, Guangsong; Gai, Keke; Tang, Yazhe; Yang, Benchao; Si, Xueming
Summary: With the development and popularization of Internet technology, network security has become the focus of attention. Vulnerabilities and back doors are regarded as two of the main reasons of network security problems. Dynamic heterogeneous redundant (DHR) architecture is a typical framework of cyberspace mimic defense. It can make use of untrusted hardware and software components to construct a high reliable and high security information system. In this article, a mathematical model is set up for the DHR architecture, and the system security is characterized by vulnerability consistency rate and success rate of system attack. The antiattack ability of the DHR system is analyzed using the mathematical model.